Comparative Study of Techniques for Alleviating Class Imbalance in Spam Classification - Waja, Gopalkrishna (International Journal of Computer Sciences and Engineering, 2021)
Class Imbalance is inarguably one of the most significant and common problem faced while training supervised machine learning models to identify anomalies. In paradigms like spam filtering, medical diagnosis, intrusion detection etc. the amount of data available on negative class is much greater than that on the positive class and hence training traditional machine learning model on such data biases it in favor of the negative class at the cost of the positive class leading the model to give a false sense of accuracy and hence undermine its own purpose. Owing to the importance of this problem several techniques have been developed to tackle it and this paper is aimed to provide an empirical comparative evaluation of a gamut of these techniques to mitigate the adverse effect of class imbalance pertaining to spam classification. In this paper I have compared the effect of 8 resampling techniques including ROS, SMOTE, ADASYN, Near-Miss and TOMEK-LINKS on the performance of eight different learning classifiers which were selected cautiously to incorporate diverse strategies used for classification. In addition to this the performance of four Ensemble learning methods, including EasyEnsemble and SMOTEBoost, are contrasted when trained on an imbalanced dataset. The AUC-ROC performance metric calculated using a stratified 5-fold cross validation was used to evaluate the effect of different imbalance handling techniques. Furthermore, Statistical tests were performed on the results obtained to posit the best model for spam classification for the dataset used.